Wear mechanism of a novel AlSiMgAl2O4Al2O3 composite used in the low vessel of an RH secondary refining furnace. Issue 9 (15th June 2019) - Ma, Chenhong; Li, Yong; Zhang, Lixin; Sun, Yang; Sun, Jialin
Abstract: A novel AlSiMgAl2 O4 Al2 O3 composite brick was prepared and evaluated in the low vessel of an RH (the initials of Ruhrstahl and Hereaeus) secondary refining furnace; it was characterized by X-ray diffraction, scanning electron microscopy, and energy-dispersive spectroscopy. The results show that after use, the AlSiMgAl2 O4 Al2 O3 composite has a functional gradient with an erosion zone–reinforced zone–original zone phase distribution, in which the phases in the erosion zone (0–1.8 cm) are a Mg-hercynite spinel solid solution, α-Al2 O3, and minor amount of Al3 Fe5 O12 . Furthermore, the phases in the reinforced zone (1.8–5.0 cm) are γ-AlON, 21RSiAlON, SiC, Mg0.388 Al2.408 O4, and α-Al2 O3 ; i.e., the Al and Si in the composite are completely converted into non-oxide reinforced phases. Finally, the phases in the original zone (>5.0 cm) show no change. The reaction mechanism is as follows. During operation, a Mg-hercynite spinel solid solution is formed in the erosion zone due to a reaction between MgAl2 O4 and FeO from a refinery operation. Therefore, the slag erosion of the material is improved. The Al and Si metals undergo active oxidation, and 21RSiAlON flakes are subsequently formed from the products of the metastable Al2 O(g), SiO(g), and N2 (g) in the ambient. The γ-AlON is formed by a carbothermal reduction nitridation of the α-Al2 O3 and residual active carbon from the resin binder. The 21RSiAlON and γ-AlON reinforce the composite brick and improve its high temperature performance accordingly. Its service life is 110% that of the magnesia-chrome bricks used in the same period. The reaction model was also established.